The Structural Combination of SIL and MODAG Scaffolds Fails to Enhance Binding to α-Synuclein but Reveals Promising Affinity to Amyloid β - Adriana Di Nanni; Ran Sing Saw; Gregory D. Bowden; Natasha S. R. Bidesi; Kaare Bjerregaard-Andersen; Špela Korat; Matthias M. Herth; Bernd J. Pichler; Kristina Herfert; Andreas Maurer (Molecules, 2023)
A technique to image α-synuclein (αSYN) fibrils in vivo is an unmet scientific and clinical need that would represent a transformative tool in the understanding, diagnosis, and treatment of various neurodegenerative diseases. Several classes of compounds have shown promising results as potential PET tracers, but no candidate has yet exhibited the affinity and selectivity required to reach clinical application. We hypothesized that the application of the rational drug design technique of molecular hybridization to two promising lead scaffolds could enhance the binding to αSYN up to the fulfillment of those requirements. By combining the structures of SIL and MODAG tracers, we developed a library of diarylpyrazoles (DAPs). In vitro evaluation through competition assays against [3H]SIL26 and [3H]MODAG−001 showed the novel hybrid scaffold to have preferential binding affinity for amyloid β (Aβ) over αSYN fibrils. A ring-opening modification on the phenothiazine building block to produce analogs with increased three-dimensional flexibility did not result in an improved αSYN binding but a complete loss of competition, as well as a significant reduction in Aβ affinity. The combination of the phenothiazine and the 3,5-diphenylpyrazole scaffolds into DAP hybrids did not generate an enhanced αSYN PET tracer lead compound. Instead, these efforts identified a scaffold for promising Aβ ligands that may be relevant to the treatment and monitoring of Alzheimer’s disease (AD).